Pengembangan Media Pembelajaran Berbasis Autoplay Media Studio pada Mata Pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) Kelas V Madrasah Ibtidaiyah Al Mujahidin Samarinda - Rismawati, Risty; Idris, Husni; Khatimah, Khusnul (Borneo Journal of Primary Education, 2025)
This research is motivated by the rapid development of technology that demands an increasein the quality of human resources, including in education. In MI Al Mujahidin Samarinda,IPAS learning is still limited to printed books and students have difficulty understanding thematerial. This study aims to develop autoplay-based learning media and what percentage ofthe validity of Autoplay Media Studio-based IPAS learning media for grade V MI AlMujahidin Samarinda to facilitate student understanding.The method used in this research is the Research and Development (R&D) method. Theresearch design model used in this study is the ADDIE (Analyze, Design, Development,Implementation, Evaluation) research and development model which has 5 stages. However,it is simplified based on the needs of researchers into 4 stages, namely ADDE (Analyze,Design, Development, Evaluation) Data collection in this study was carried out byobservation to obtain information on the location, conditions, and facilities and infrastructureof the school, distributing questionnaires to media experts to determine the feasibility level ofthe product then to see the level of validity of the autoplay media product, distributingquestionnaires to students and documentation as evidence of the questionnaire distributionprocess. This research was conducted at MI Al Mujahidin Samarinda in classes VA and VB.Based on the results of research and data analysis, it shows that the Autoplay Media Studiobased Learning Media on IPAS Class V Subjects MI Al Mujahidin Samarinda that has beendeveloped is said to be very feasible to be tested in the field by material experts and mediaexperts with a percentage of material expert assessment of 84.09% and media expertassessment of 96.25%. The results of the readability test in small groups amounted to 89.7%and large groups amounted to 87.08%. This indicates that the Autoplay Media Studio-basedLearning Media on Natural and Social Sciences (IPAS) Class V MI Al Mujahidin Samarindaproduced in this study is declared very feasible to be applied in IPAS learning.